Simulated resumption of the North Atlantic meridional overturning circulation – Slow basin-wide advection and abrupt local convection - Renold, Manuel; Raible, Christoph C.; Yoshimori, Masakazu; Stocker, Thomas F. (Quaternary Science Reviews, 2010)
The resumption process of the North Atlantic meridional overturning circulation (MOC) is investigated in a series of freshwater hosing experiments using a comprehensive coupled climate model. Four different freshwater perturbations are applied to the North Atlantic between 50°N and 70°N leading to a substantial weakening of MOC and an expansion of winter sea ice cover over the Greenland–Iceland–Norwegian (GIN) Seas. Deactivating the freshwater forcing leads to a two-phase recovery of the MOC. The first phase is a slow basin-wide advection process whereas the second phase is an abrupt, decadal-scale transition, located in the North Atlantic. The slow basin-wide advection process to an intermediate state of the MOC is characterized by a restart of the deep water production in the area of the subpolar gyre and the Irminger Basin. However, the ice cover over the GIN Seas remains, whereas the surface density gradually increases in the GIN Seas on a century time scale. The length of this intermediate state depends on the strength of freshwater perturbation, which determines the magnitude of the meridional density gradient in the North Atlantic. The second transition phase is triggered by a model-specific density threshold reached in the GIN Seas. When passed, the MOC abruptly intensifies by ∼60% within 60–80 years. The analysis shows that this abrupt intensification only depends on surface salinity in the GIN Seas. The model results reveal that the simulated sea ice retreat in the GIN Seas and a rapid increase of the Greenland air temperature of the second phase of the resumption of the MOC are similar in amplitude to temperature proxies observed during Dansgaard–Oeschger events of the last ice age.